Morphometry of right ventricular hypertrophy induced by myocardial infarction in the rat. - Anversa, P. (1984)
The growth response of the right ventricle was studied in rats following ligation of the left coronary artery, which produced infarcts comprising approximately 40% of the left ventricle. A month after surgery the weight of the right ventricle was increased 30%, and this hypertrophic change was characterized by a 17% wall thickening, consistent with the 13% greater diameter of myocytes. Myocardial hypertrophy was accompanied by an inadequate growth of the microvasculature that supports tissue oxygenation. This was seen by relative decreases in capillary luminal volume density (-27%) and capillary luminal surface density (-21%) and by an increase in the average maximum distance from the capillary wall to the mitochondria of myocytes (19%). In contrast, measurements of the mean myocyte volume per nucleus showed a proportional enlargement of these cells (32%), from 16,300 cu mu in control animals to 21,500 cu mu in experimental rats. Quantitative analysis of the right coronary artery revealed a 33% increase in its luminal area, commensurate with the magnitude of ventricular hypertrophy.